Mamma mia! : here we go again [videorecording (Blu-Ray + DVD)] - Parker, Ol, 1969-; Parker, Ol, 1969-; Seyfried, Amanda; Streep, Meryl; James, Lily, 1989-; Garcia, Andy; Cher, 1946-; Brosnan, Pierce; Firth, Colin, 1960-; Skarsgård, Stellan; Walters, Julie, 1950-; Cooper, Dominic, 1978-; et al. (Universal Pictures Home Entertainment, 2018)
As Sophie prepares for a hotel re-opening, she reflects on her mother's journey in life and realizes they are similar in unexpected ways.